White matter abnormalities of the frontal–striatal–thalamic circuit in individuals with attenuated positive symptom syndromes: a probabilistic tractography study - Zhenzhu Chen; Qijing Bo; Lei Zhao; Yushen Ding; Yimeng Wang; Qitong Jiang; Feng Li; Yuan Zhou; Chuanyue Wang (Schizophrenia)
Abstract Attenuated positive symptoms syndrome (APSS) is a risk state preceding psychosis, and its early identification is key to early intervention. Previous studies have suggested that disturbances in the frontal–striatal–thalamic (FST) circuit may play a role in the neuropathology of APSS. However, the evidence regarding white matter structure remains fragmented. This study aimed to systematically investigate white matter (WM) alterations within the FST circuits in individuals with APSS. Diffusion magnetic resonance imaging (dMRI) and T1-weighted images were acquired from 43 individuals with APSS and 50 healthy controls (HCs). The dMRI data were preprocessed using FMRIB Software Library software. The Brainnetome Atlas was utilized to extract regions of interest (ROIs) in the frontal lobe, striatum, and thalamus. Bidirectional probabilistic tractography was performed to construct the FST circuit. The connection probability (CP) and diffusion index values were compared between the APSS and HC groups using the two-sample t test. Compared to HCs, individuals with APSS exhibited significantly lower CP values in right orbital gyrus_area 13- right nucleus accumbens (OrG_A13-NAC) fiber tract; higher mean diffusivity values in the left OrG_A13-NAC and left ventral caudate–left caudal temporal thalamus (vCa-cTtha) fiber tracts; higher radial diffusivity values in the right OrG_A13-NAC fiber tract; and higher axial diffusivity values in multiple frontal lobe ROI–striatum ROI and striatum ROI–thalamus ROI fiber tracts. Overall, individuals with APSS demonstrated white matter microstructural abnormalities, especially in the OrG_A13-NAC fiber tracts. These alterations may contribute to our understanding on the neuropathology of APSS.